Foreign body (copper wire) in urinary bladder and urethra: an unusual case presentation - Bansal, Nipun; Mahajan, Anuj; Shetty, Manjunath; Adiga, Prashanth; Raj, Kishan; Moolya, Chetna (International Surgery Journal, 2021)
Foreign bodies are rarely reported in the urinary bladder and urethra; though it is a topic of curiosity amongst the urologists and surgeon. In majority of the cases, the foreign body is removed via the transurethral approach. A 19-year-old young male patient was brought to our Institution with history of insertion of a wire through urethra during act of masturbation in the middle of night. Patient was having severe pain in penis along with burning micturition. Patient was taken up in emergency for retrieval of the foreign body (wire) transurethrally (cystoscopic approach). Scope was inserted through urethra and the foreign body retrieved was found to be “copper wire”.